Head Lice of Pygmies Reveal the Presence of Relapsing Fever Borreliae in the Republic of Congo. - Nadia Amanzougaghene; Jean Akiana; Géor Mongo Ndombe; Bernard Davoust; Nardiouf Sjelin Nsana; Henri-Joseph Parra; Florence Fenollar; Didier Raoult; Oleg Mediannikov (Public Library of Science (PLoS), 2016)
BACKGROUND:Head lice, Pediculus humanus capitis, occur in four divergent mitochondrial clades (A, B, C and D), each having particular geographical distributions. Recent studies suggest that head lice, as is the case of body lice, can act as a vector for louse-borne diseases. Therefore, understanding the genetic diversity of lice worldwide is of critical importance to our understanding of the risk of louse-borne diseases. METHODOLOGY/PRINCIPAL FINDINGS:Here, we report the results of the first molecular screening of pygmies' head lice in the Republic of Congo for seven pathogens and an analysis of lice mitochondrial clades. We developed two duplex clade-specific real-time PCRs and identified three major mitochondrial clades: A, C, and D indicating high diversity among the head lice studied. We identified the presence of a dangerous human pathogen, Borrelia recurrentis, the causative agent of relapsing fever, in ten clade A head lice, which was not reported in the Republic of Congo, and B. theileri in one head louse. The results also show widespread infection among head lice with several species of Acinetobacter. A. junii was the most prevalent, followed by A. ursingii, A. baumannii, A. johnsonii, A. schindleri, A. lwoffii, A. nosocomialis and A. towneri. CONCLUSIONS/SIGNIFICANCE:Our study is the first to show the presence of B. recurrentis in African pygmies' head lice in the Republic of Congo. This study is also the first to report the presence of DNAs of B. theileri and several species of Acinetobacter in human head lice. Further studies are needed to determine whether the head lice can transmit these pathogenic bacteria from person to another.